A test case for implementing feedback control in a micro hydro power plant - Suliman, Ahmad (Kansas State University, 2010)
Micro-hydro turbines generate power for small villages and industries in Afghanistan. They usually produce less than 100 kW of power. Currently the flow into the turbine is controlled manually and the voltage is controlled automatically with an electronic load controller. Excess power not used by the village is dumped into a community water heater. For larger sites that have a reservoir and/or large variable load throughout the day and night, the turbine needs to be fitted with an automatic flow control system to conserve water in the reservoir or deal with the variable loads. Large turbines usually use hydraulic governors that automatically adjust the flow of water into the turbine. For micro-hydro sized plants this method would be too expensive and be difficult to build and maintain locally. For this reason, a 3 phase AC induction motor will be used to move the internal flow control valve of the turbine. Because a sudden change in load is possible (30 – 40%) for micro-hydro plants, the electronic load controller will also be needed to respond to quick changes in load so that the village voltage does not exceed 220V. This report documents the process of building a test system comprising of a dynamic resistive load, microcontroller controlled resistive load, a three phase AC generator and a DC Motor. Where the dynamic resistive load represents the load of the village, the computer controlled resistive load would represent the community water heater, the three phase AC generator represents the Generator on site and the DC Motor together with its DC input voltage would emulate the turbine and its water flow respectively. The DC input voltage would be also controlled with a PWM signal through a delay loop to represent the water gate delay effects on the turbine as close as possible. With this, it would be possible to completely build and test a control system that emulates the dynamics of a water turbine generator.
Keywords: Power systems; Micro hydro; Frequency stabilization; Multi rate speed control in micro hydro; Dump resistive load controller; Computer based frequency measurement; Engineering, Electronics and Electrical (0544)